Cechy charakteru czy kompetencje i umiejętności - dylematy rodzica XXI wieku - Jezierska-Wiejak, Elżbieta (Karkonoska Państwowa Szkoła Wyższa, 2012)
Who do we want to educate? Happy, kind and trustworthy people or perhaps individuals equipped with many competences and skills – this is a dilemma of contemporary parents, teachers, and educators. From the analysis of interviews with parents whose children start their first year in nursery school there emerges a disturbing vision of the characteristics of the contemporary man. Globalisation questions the process of forming such traits as kindness, authenticity, and beauty, which shape morality. Instead of this triad that determines the relations between people as well as between people and the world, some specific competencesand skills are preferred in the education of children.
Keywords: features; competencies; developing skills; family; aid